2016
DOI: 10.1136/neurintsurg-2016-012324
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining door to recanalization processes in endovascular stroke therapy

Abstract: This pilot study demonstrates that D2P times can be significantly reduced with a standardized multidisciplinary approach. There was no significant difference in the rate of 3-month good outcome, which is most likely due to the small sample size and confounding baseline patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Studies have shown that median or mean door-to-imaging times of ≤20 minutes can be achieved in a variety of different hospital settings. [74][75][76] See Table XVI in online Data Supplement 1. …”
mentioning
confidence: 99%
“…Studies have shown that median or mean door-to-imaging times of ≤20 minutes can be achieved in a variety of different hospital settings. [74][75][76] See Table XVI in online Data Supplement 1. …”
mentioning
confidence: 99%
“…8 With an emphasis on parallel workflow, preset time goals, and continuous feedback, several centers have now demonstrated improved treatment times with quality-initiative projects. 17,18 Based on their meta-analysis, Saver et al 8 advocate for the following time metrics: 50 minutes for brain imaging-to-arterial puncture time, 75 minutes for ED door-to-arterial puncture time, and 110 minutes for ED door-to-reperfusion time.…”
Section: Discussionmentioning
confidence: 99%
“…This has also held true in the modern embolectomy era 7. Workflow optimization to ensure rapid triage of patients with severe stroke and efficient in-hospital processes are vital to optimize time to angiography 8 9. Our aim was to standardize what happened intraprocedurally once the patient arrived in the angiography suite and to examine how this impacted time from groin puncture to first deployment and recanalization.…”
Section: Introductionmentioning
confidence: 99%